Transmission conductor coating with passive cooling and capacity increasing functions and process

By using transmission wire coatings with passive cooling and capacity enhancement functions, using materials such as manganese zinc ferrite nanoparticles and hollow glass microbeads, the problem of fluctuations in heat dissipation performance of wire coatings in complex environments is solved, and a higher level of High current carrying capacity and better weather resistance.

CN119410182APending Publication Date: 2025-02-11STATE GRID HUBEI EXTRA HIGH VOLTAGE CO +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411846814.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

In the prior art, under large current carrying capacity fluctuations and complex operating environments, the thermal dissipation performance of the wire coating fluctuates greatly, affecting the weather resistance and the upper limit of the current carrying capacity.

Method used

It adopts a transmission conductor coating with passive cooling and capacity enhancement function. The coating consists of component A and component B. Component A contains manganese zinc ferrite nanoparticles, terminal hydroxydimethylpolysiloxane and other materials. Component B contains hollow glass microbeads, glass powder, etc., and is processed through mixing and stirring and a specific process to form a coating with excellent heat dissipation and reflective properties.

Benefits of technology

In the environment of large current carrying capacity fluctuations and complex operation, a large current carrying capacity upper limit is maintained, and the current carrying capacity upper limit of the wire is further improved by reflecting sunlight and increasing the heat dissipation effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410182A_ABST
    Figure CN119410182A_ABST
Patent Text Reader

Abstract

The invention provides a power transmission conductor coating with passive cooling and capacity increasing functions and a process, belongs to the technical field of power transmission conductors, and solves the technical problems that the existing coating cannot well adapt to a complex operation environment of a high-voltage power transmission conductor and the like. According to the power transmission conductor coating with the passive cooling and compatibilizing functions, the hydroxyl dimethyl polysiloxane, the silicon nitride, the polyethylene resin and the mica micro powder of the component A are matched, so that the heat dissipation performance of the coating can be improved, the solidification is relatively fast, and the effect of efficiently and rapidly establishing a heat dissipation coating can be rapidly achieved; and a coating formed by the raw materials such as the hollow glass beads and the glass powder of the component B can reflect visible light and near-infrared light in sunlight for multiple times. Compared with the prior art, the protective coating has the advantages that the heat dissipation performance of the protective coating is less affected when the current-carrying capacity fluctuation is relatively large and the operation environment is complex, so that the protective coating can always keep a relatively large current-carrying capacity upper limit, and the current-carrying capacity upper limit is improved by reflecting sunlight and improving the heat dissipation effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of power transmission wires, and relates to a coating and a process, in particular to a power transmission wire coating and a process with passive temperature reduction and capacity increase functions. Background Art

[0002] At present, most of the power conductors used in various power grids that transmit electricity from power plants to end users are made of conductive media such as copper and aluminum with good conductivity and steel core with high tensile strength through mechanical stranding. This kind of power conductor made of pure metal has fatal defects under extreme natural conditions. The current carrying capacity of high-voltage transmission conductors will be affected by the temperature of the conductors. If the high-voltage transmission conductors cannot dissipate heat quickly, the current carrying capacity of the high-voltage transmission conductors will be greatly limited. In addition, icing of overhead conductors is one of the most serious threats to the power system. The deicing methods for conductor icing are mostly mechanical deicing, thermal ice melting and passive dehydration. The so-called passive dehydration method is to coat a layer of ice-repellent material on the surface of the conductor, such as ZS-611 anti-ice and snow coating, to prevent water from adhering to the surface of the wire, thereby preventing ice on the conductor.

[0003] After searching, it is found that a Chinese patent document discloses a conductor with high current carrying capacity and anti-icing performance and a preparation method thereof [Application No.: 201410229667.9; Publication No.: CN 103985464 B]. The conductor and the preparation method thereof comprise: a conductor body (1) and a composite coating (2) coated on the outside of the conductor body (1), wherein the composite coating (2) is made of fluorocarbon coating and heat dissipation filler. The conductor provided by the present invention has a reasonable structural design, and after being sprayed with fluorocarbon coating and heat dissipation filler in a preferred ratio, it has excellent hydrophobicity and anti-icing performance, and the conductor has high heat dissipation power and large current carrying capacity, and can be widely used in harsh natural environments, and has good power transmission safety. In addition, the particle size of the heat dissipation filler, the dosage ratio of the fluorocarbon coating and the heat dissipation filler, and the thickness of the composite coating on the outer surface of the bare conductor are screened out through a large number of experiments. The entire preparation method is scientific and reasonable, and has strong operability. The prepared conductor has high current carrying capacity and anti-icing performance, and can overcome many shortcomings of the prior art.

[0004] Although the conductor disclosed in this patent has a high heat dissipation power and a large current carrying capacity through a composite coating, the composite coating is only suitable for operating environments and areas with relatively stable current carrying capacity, and cannot adapt well to the complex operating environment of high-voltage transmission conductors. When the current carrying capacity of the transmission conductor and the temperature of the conductor change greatly, the heat dissipation performance of the coating fluctuates greatly and will greatly affect its weather resistance, thereby causing the upper limit of the current carrying capacity of the conductor to vary greatly. Summary of the invention

[0005] The purpose of the present invention is to address the above-mentioned problems in the existing technology and propose a transmission wire coating and process with passive temperature reduction and capacity increase functions. The technical problem to be solved by the invention is: how to ensure that the heat dissipation performance of the protective coating is less affected when the current carrying capacity fluctuates greatly and the operating environment is complex, so that it can always maintain a large upper limit of current carrying capacity, and at the same time, increase the upper limit of current carrying capacity by reflecting sunlight and increasing the heat dissipation effect.

[0006] The purpose of the present invention can be achieved by the following technical solutions: A transmission line coating with passive temperature reduction and capacity increase functions comprises component A and component B, wherein component A is composed of the following raw materials in parts by mass: 10-25 parts of manganese zinc ferrite nanoparticles, 25-40 parts of terminal hydroxy dimethyl polysiloxane, 10-20 parts of nano silicon dioxide, 8-15 parts of silicon nitride, 2-8 parts of mica micropowder, 10-20 parts of polyethylene resin, 50-70 parts of dihydroxy tetra-active hydrogen unsaturated siloxane, 7-13 parts of isocyanate, and 6-14 parts of fatty acid ester; and component B is composed of the following raw materials in parts by mass: 3-8 parts of silane coupling agent, 4-10 parts of aluminate coupling agent, 15-20 parts of hollow glass microspheres, 1-3 parts of methacryloyl chromium complex and 20-30 parts of glass powder, 2-6 parts of curing agent, and 1-4 parts of leveling agent.

[0007] Component A is composed of the following raw materials in parts by mass: 13 parts of manganese zinc ferrite nanoparticles, 33 parts of terminal hydroxy dimethyl polysiloxane, 15 parts of nano silicon dioxide, 11 parts of silicon nitride, 5 parts of mica powder, 15 parts of polyethylene resin, 60 parts of dihydroxy tetraactive hydrogen unsaturated siloxane, 10 parts of isocyanate, and 10 parts of fatty acid ester; Component B is composed of the following raw materials in parts by mass: 5 parts of silane coupling agent, 7 parts of aluminate coupling agent, 17 parts of hollow glass microspheres, 2 parts of methacryloyl chromium complex and 25 parts of glass powder, 4 parts of curing agent, and 3 parts of leveling agent.

[0008] The particle size of the manganese zinc ferrite nanoparticles ranges from 100 to 200 nm.

[0009] The weight average molecular weight of the dihydroxy tetra-active hydrogen unsaturated siloxane is 3500-7500.

[0010] A process for coating a power transmission conductor with passive temperature reduction and capacity increase functions comprises the following steps: S1, adding manganese zinc ferrite nanoparticles into a grinder, and adding 5%-25% oleic acid for mixed grinding, drying the residual liquid of the product after grinding, and collecting it by adsorption with a magnetic material to obtain manganese zinc ferrite nanopowder after drying; S2, adding terminal hydroxy dimethyl polysiloxane, nano silicon dioxide, silicon nitride, and mica powder into a mixer, mixing and stirring, and filtering to obtain a first mixed material; S3, after the mixer is rinsed and dried, polyethylene resin, dihydroxy tetra-active hydrogen unsaturated siloxane, isocyanic acid and fatty acid ester are added to the mixer for mixing reaction, the reaction time is 100-160min, the reaction temperature is 50-70°C, and the second mixture is obtained; S4, re-weighing and proportioning the manganese-zinc ferrite nanopowder, the first mixed material and the second mixed material according to parts by mass, and setting aside; S5. After the mixer is rinsed and dried again, the proportioned manganese-zinc ferrite nano powder, the first mixed material and the second mixed material are added into the mixer, mixed and stirred to obtain a finished protective coating.

[0011] In step S5, the stirring speed is 200-450 rpm, the stirring time is 50-75 min, and the stirring temperature is 30-45°C.

[0012] The equipment used in the steps S1-S5 is a protective coating processing device, which includes a grinder and a mixer, wherein the discharge port of the grinder is connected to a first material storage box, the upper end of the mixer is fixed with a first weighing box and a second weighing box through a feed pipe, the first material storage box is connected to the first weighing box through a first conveying component, the discharge port of the mixer is connected to a second material storage box and a third material storage box through a discharge pipe, the second material storage box is connected to the second weighing box through a second conveying component, the third material storage box is connected to the second weighing box through a third conveying component, a stirring component is arranged inside the mixer, a filter screen is fixed inside the mixer, a sewage pipe and a slag discharge pipe are fixed on the side of the mixer, a feed hopper is fixed at the upper end of the mixer, a water adding pipe is fixed at the upper end of the mixing box, a spray seat is fixed at the upper end of the mixing box, the spray seat is connected to the water adding pipe, the water adding pipe is connected to an external high-pressure water pump, and a drying unit is arranged inside the mixing box.

[0013] With the above structure, during operation, manganese zinc ferrite nanoparticles are added into a grinder, and 5%-25% oleic acid is added for mixed grinding. After grinding, the residual liquid of the product is dried, and after drying, it is adsorbed and collected by a magnetic material to obtain manganese zinc ferrite nanopowder, and sent to a first storage box for storage. At the same time, terminal hydroxy dimethyl polysiloxane, nano silicon dioxide, silicon nitride, and mica powder are added into the mixer for mixed stirring, and filtered. The first mixed material is sent to a second storage box, and then the external high-pressure water pump is turned on, and the high-pressure cleaning liquid is sent into the spray seat through the water supply pipe. The mixer is cleaned by the spray seat in combination with the stirring assembly, and the sewage pipe and the slag discharge pipe are opened at the same time to discharge the impurities filtered on the filter screen and the sewage generated by the cleaning, and then the drying unit is used for drying. After drying, polyethylene resin, dihydroxy tetra-active hydrogen unsaturated siloxane, isocyanic acid and fatty acid ester are added to the mixer for mixing reaction. The reaction time is 100-160min and the reaction temperature is 50-70°C. The second mixture is then sent to the third storage box for storage. The mixer is rinsed and dried again using the spray seat and the drying unit. The manganese zinc ferrite nano powder is sent to the first weighing box through the first conveying component, and the first mixture is sent to the mixing box through the second conveying unit. After weighing according to the proportion, the manganese zinc ferrite nano powder and the first mixture are added to the mixer for mixing and stirring. At the same time, the second mixture is sent to the second weighing box using the third conveying component. After weighing, it is added to the mixer for mixing and stirring to obtain a finished protective coating.

[0014] A feeding hopper is fixed on the upper end of the grinder, a grinding motor is fixed on the upper end of the grinder, a rotating cylinder is fixed on the output shaft end of the grinding motor, a rotating column is slidably connected to the inside of the rotating cylinder through a slide rail, a grinding seat is fixed on the lower end of the rotating column, a screening plate matched with the grinding seat is fixed to the inside of the grinder, the screening holes on the screening plate are distributed in a ring-shaped manner in multiple rows, a sealing mechanism matched with the screening plate is arranged inside the grinder, a material cavity is formed between the lower side of the screening plate and the grinder, a connecting port is opened between the first material storage box and the material cavity, a rotating motor is fixed inside the grinder, a circular plate located in the connecting port is fixed on the output shaft end of the rotating motor, a plurality of magnetic plates and non-magnetic plates are fixed on the outer periphery of the circular plate, the magnetic plates and the non-magnetic plates are arranged alternately, a scraper cover is fixed inside the first material storage box, the inner side of the scraper cover is in contact with the magnetic plate and the non-magnetic plate The upper and lower surfaces are in conflict with each other, and a number of leakage holes are provided on the non-magnetic plate. A number of first heating rods are fixed inside the grinding seat, and a number of screw conveyors are fixed inside the grinding seat. The lower ends of the spiral conveying blades of the screw conveyors extend out of the lower end of the grinding seat, and the discharge port of the screw conveyor is located at the inner upper part of the grinder. An annular seat is fixed inside the grinder, and a guide groove is provided on the inner periphery of the annular seat. A number of guide rods are fixed on the outer periphery of the grinding seat, and the guide rods are slidably connected to the guide groove. The guide groove includes a first straight section, a second straight section, an ascending section and a descending section, and the two ends of the second straight section are respectively connected to the ascending section and the descending section, and the other ends of the ascending section and the descending section are connected to the first straight section. The bottom of the guide groove is an inclined mechanism, and an inclined discharge port is provided at the bottom of the guide groove. The cross-section of the guide rod mixer part is the same as the cross-section of the guide groove.

[0015] With the above structure, during operation, the manganese-zinc-ferrite nanoparticles are added into the grinder through the feeding hopper, and then 5%-25% oleic acid is added, and the grinding motor is turned on at the same time. The grinding motor drives the grinding seat to rotate through the rotating cylinder and the rotating column, and the manganese-zinc-ferrite nanoparticles are ground by the cooperation of the grinding seat and the screening plate. When the grinding seat rotates, it drives the guide rod to slide in the guide groove. The ascending section and the descending section of the guide groove are connected. Under the action of the ascending section and the descending section, the grinding seat is driven to move up and down intermittently, so that the manganese-zinc-ferrite nanoparticles with large particle size enter between the grinding seat and the screening plate. At the same time, the descent of the grinding seat can also be used to squeeze the manganese-zinc-ferrite nanoparticles, which greatly improves the grinding efficiency and grinding effect. At the same time, the screw conveyor is intermittently turned on to transport the manganese-zinc-ferrite nanoparticles between the grinding seat and the screening plate to the top of the material, so that other manganese-zinc-ferrite nanoparticles can be In order to obtain grinding and ensure the uniformity of grinding, after the grinding is completed, the first heating rod is turned on to dry the residual liquid in the manganese-zinc ferrite nano powder, after the drying is completed, the blocking mechanism is turned on to make the manganese-zinc ferrite nano powder fall from the screening hole into the material chamber, and at the same time, the rotating motor is turned on to drive the magnetic plate and the non-magnetic plate to rotate, and the manganese-zinc ferrite nano powder is collected by the magnetic plate, and then after rotating into the first storage box, the manganese-zinc ferrite nano powder on the magnetic plate is scraped off by the scraping cover and falls into the first storage box, completing the magnetic separation operation of the manganese-zinc ferrite nano powder and ensuring the purity of the manganese-zinc ferrite nano powder. The structure has good collection effect and high efficiency. At the same time, the interval between the magnetic plate and the non-magnetic plate makes the manganese-zinc ferrite nano powder in the material chamber have a certain up and down oscillation, so that other substances on the manganese-zinc ferrite nano powder can be shaken off, further improving the quality of the manganese-zinc ferrite nano powder.

[0016] The sealing assembly includes a sealing frame, an outer gear ring is fixed on the outer periphery of the sealing frame, an annular groove is opened inside the grinder, the outer gear ring is rotatably connected to the annular groove, a driving motor is fixed inside the grinder, a driving gear is fixed on the output shaft end of the driving motor, the driving gear is meshed with the outer gear ring, and the annular frame is composed of a plurality of sealing plates distributed in an annular shape.

[0017] With the above structure, when the manganese-zinc ferrite nanoparticles are ground, the blocking plate blocks the screening holes on the screening plate. After the grinding is completed, the driving motor drives the driving gear to rotate, and the driving gear drives the blocking frame to rotate through the outer gear ring, so that the blocking plate deviates from the screening hole, so that the manganese-zinc ferrite nanopowder after grinding can fall. The structure is simple, the degree of automation is high, and the difficulty of the work is reduced.

[0018] The feed pipe and the feed hopper are both provided with a cleaning assembly, and the cleaning assembly includes a second heating rod. The side walls of the feed pipe and the feed hopper are both provided with a cleaning cavity, the second heating rod is fixed in the cleaning cavity, an electromagnetic block is fixed inside the cleaning cavity, a spring is fixed on the electromagnetic block, and a knocking block is fixed to the other end of the spring.

[0019] With the above structure, after the feeding is completed, the second heating rod can be turned on to heat the feed pipe and the feed hopper, and the material remaining on the inner wall of the feed pipe and the feed hopper can be dried. At the same time, the electromagnet is intermittently powered on and off, and the spring is used to make the knocking block knock on the feed pipe and the feed hopper, so that the feed pipe and the feed hopper vibrate, thereby shaking off the material remaining on the inner wall of the feed pipe and the feed hopper. The setting of this structure can, on the one hand, ensure that the feed pipe and the feed hopper are not blocked by the material remaining on the inner wall for a long time, and on the other hand, prevent the material remaining on the inner wall of the feed pipe and the feed hopper from affecting the processing quality.

[0020] Compared with the existing technology, the transmission wire coating and process with passive temperature reduction and capacity increase function has the following advantages: 1. The power transmission line coating and process with passive cooling and capacity increasing functions of the present invention have a scientific and reasonable ratio, can give full play to the performance of each component raw material, and the processing technology is simple, can greatly reduce the influence of material loss on the protective coating during the processing, and ensure the processing accuracy of the protective coating during production, and the coating is divided into component A and component B. After the processing is completed, component A and component B are stored separately. When in use, component A is first coated on the high-voltage transmission line conductor, and the manganese zinc ferrite nanomaterial and nano silicon dioxide of component A are used to make the coating have active groups or show hydrophobic properties, so that the transmission line has excellent anti-icing or anti-frost performance, and the accumulated ice can be removed under the irradiation of sunlight only by natural conditions such as wind and gravity. The combination of hydroxydimethylpolysiloxane, silicon nitride, polyethylene resin, and mica powder can not only improve the heat dissipation performance of the coating, but also solidify faster, and can quickly achieve high efficiency, The effect of the heat dissipation coating is quickly established. After the coating of component A is completed, component B is coated on the surface of component A in a linear state. The coating of component B is distributed in a ring with multiple coating lines on the surface of component A. This setting will not affect the passive heat dissipation effect of component A. The coating formed by the hollow glass beads, glass powder and other raw materials in component B can also be used to reflect the visible light and near-infrared light in the sunlight multiple times, so that the coating with added glass beads has very good heat reflection performance, further improving the heat dissipation performance of high-voltage transmission lines, thereby increasing the upper limit of the current carrying capacity of high-voltage transmission lines.

[0021] 2. During operation, add manganese zinc ferrite nanoparticles into the grinder, and add 5%-25% oleic acid for mixed grinding. After grinding, dry the residual liquid of the product, collect it by adsorption with magnetic material after drying to obtain manganese zinc ferrite nanopowder, and send it into the first storage box for storage. At the same time, add terminal hydroxy dimethyl polysiloxane, nano silicon dioxide, silicon nitride, and mica powder into the mixer for mixed stirring, and filter it. Send the first mixed material into the second storage box, then start the external high-pressure water pump, send the high-pressure cleaning liquid into the spray seat through the water pipe, use the spray seat to cooperate with the stirring component to clean the mixer, and at the same time open the sewage pipe and the slag discharge pipe to discharge the impurities filtered on the filter screen and the sewage generated by cleaning, and then use the drying unit to dry it. After drying, Finally, polyethylene resin, dihydroxy tetra-active hydrogen unsaturated siloxane, isocyanic acid and fatty acid ester are added to the mixer for mixing reaction. The reaction time is 100-160min and the reaction temperature is 50-70°C. The second mixture is then sent to the third storage box for storage. The mixer is rinsed and dried again by the spray seat and the drying unit. The manganese zinc ferrite nano powder is sent to the first weighing box through the first conveying component, and the first mixture is sent to the mixing box through the second conveying unit. After weighing according to the proportion, the manganese zinc ferrite nano powder and the first mixture are added to the mixer for mixing and stirring. At the same time, the second mixture is sent to the second weighing box by the third conveying component. After weighing, it is added to the mixer for mixing and stirring to obtain a finished protective coating.

[0022] 3. During operation, the manganese-zinc-ferrite nanoparticles are added into the grinder through the feeding hopper, and then 5%-25% oleic acid is added, and the grinding motor is turned on at the same time. The grinding motor drives the grinding seat to rotate through the rotating cylinder and the rotating column, and the manganese-zinc-ferrite nanoparticles are ground by the cooperation of the grinding seat and the screening plate. When the grinding seat rotates, it drives the guide rod to slide in the guide groove, and the ascending section and the descending section of the guide groove are connected. Under the action of the ascending section and the descending section, the grinding seat is driven to move up and down intermittently, so that the manganese-zinc-ferrite nanoparticles with large particle size enter between the grinding seat and the screening plate. At the same time, the descent of the grinding seat can also be used to squeeze the manganese-zinc-ferrite nanoparticles, which greatly improves the grinding efficiency and grinding effect. At the same time, the screw conveyor is intermittently turned on to transport the manganese-zinc-ferrite nanoparticles between the grinding seat and the screening plate to the top of the material, so that other manganese-zinc-ferrite nanoparticles can be ground to ensure the uniformity of grinding.

[0023] 4. After the grinding is completed, the first heating rod is turned on to dry the residual liquid in the manganese-zinc ferrite nanopowder. After the drying is completed, the blocking mechanism is turned on to make the manganese-zinc ferrite nanopowder fall from the screening hole into the material chamber, and the rotating motor is turned on at the same time. The rotating motor drives the magnetic plate and the non-magnetic plate to rotate, and the manganese-zinc ferrite nanopowder is collected by the magnetic plate. After it is rotated into the first storage box, the manganese-zinc ferrite nanopowder on the magnetic plate is scraped off by the scraper cover and falls into the first storage box, completing the magnetic separation operation of the manganese-zinc ferrite nanopowder to ensure the purity of the manganese-zinc ferrite nanopowder. The structure has good collection effect and high efficiency. At the same time, the interval between the magnetic plate and the non-magnetic plate makes the manganese-zinc ferrite nanopowder in the material chamber have a certain up and down oscillation, so that other substances on the manganese-zinc ferrite nanopowder can be shaken off, further improving the quality of the manganese-zinc ferrite nanopowder.

[0024] 5. After the feeding is completed, the second heating rod can be turned on to heat the feeding pipe and the feed hopper to dry the residual materials on the inner walls of the feeding pipe and the feed hopper. At the same time, the electromagnet is intermittently powered on and off, and the spring is used to make the knocking block knock on the feeding pipe and the feed hopper, so that the feeding pipe and the feed hopper vibrate, thereby shaking off the residual materials on the inner walls of the feeding pipe and the feed hopper. The setting of this structure can, on the one hand, ensure that the residual materials on the inner walls of the feeding pipe and the feed hopper are not blocked by long-term use, and on the other hand, prevent the residual materials on the inner walls of the feeding pipe and the feed hopper from affecting the processing quality. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a process flow chart of the present invention.

[0026] Figure 2 It is a structural schematic diagram of the protective coating processing device in the present invention.

[0027] Figure 3 It is a structural schematic diagram of the grinding machine in the present invention.

[0028] Figure 4 It is a structural schematic diagram of the annular seat in the present invention.

[0029] Figure 5 yes Figure 4 A partial enlarged view of point B in the middle.

[0030] Figure 6 It is a structural schematic diagram of the blocking mechanism in the present invention.

[0031] Figure 7 It is a structural schematic diagram of the magnetic separation part in the present invention.

[0032] Figure 8 yes Figure 3 A partial enlarged view of point A in the middle.

[0033] Fig. 9 It is a schematic diagram of the structure of the mixer in the present invention.

[0034] Fig.10 It is a structural schematic diagram of the feed hopper in the present invention.

[0035] Fig.11 This is the test table for Experimental Example 1.

[0036] Fig.12 This is the test table for the light intensity of 5000Lux in Experimental Example 2.

[0037] Fig.13 This is the test table for the light intensity of 35000Lux in Experimental Example 2.

[0038] Fig.14 This is the test table for the light intensity of 70000Lux in Experimental Example 2.

[0039] Fig.15 This is the test table for the light intensity of 100000 Lux in Experimental Example 2.

[0040] In the figure, 1, grinding machine; 2, first material storage box; 3, first conveying assembly; 4, mixer; 5, first weighing box; 6, second weighing box; 7, second material storage box; 8, third material storage box; 9, second conveying assembly; 10, third conveying assembly; 11, feeding hopper; 12, stirring assembly; 13, water adding pipe; 14, feeding hopper; 15, grinding motor; 16, rotating drum; 17, rotating column; 18, grinding seat; 19, screw conveyor; 20, screening plate; 21, blocking frame; 22, rotary Rotating motor; 23. circular plate; 24. scraper cover; 25. first heating rod; 26. annular seat; 27. guide groove; 28. guide rod; 29. ​​discharge port; 30. outer gear ring; 31. non-magnetic plate; 32. magnetic plate; 33. leakage hole; 34. driving motor; 35. driving gear; 36. spray seat; 37. filter screen; 38. slag discharge pipe; 39. sewage discharge pipe; 40. feeding pipe; 41. cleaning chamber; 42. second heating rod; 43. electromagnet; 44. spring; 45. knocking block. DETAILED DESCRIPTION

[0041] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.

[0042] Embodiment 1 A transmission line coating with passive temperature reduction and capacity increase functions, wherein component A is composed of the following raw materials in parts by mass: 13 parts of manganese zinc ferrite nanoparticles, 33 parts of terminal hydroxy dimethyl polysiloxane, 15 parts of nano silicon dioxide, 11 parts of silicon nitride, 5 parts of mica powder, 15 parts of polyethylene resin, 60 parts of dihydroxy tetraactive hydrogen unsaturated siloxane, 10 parts of isocyanate, and 10 parts of fatty acid ester; component B is composed of the following raw materials in parts by mass: 5 parts of silane coupling agent, 7 parts of aluminate coupling agent, 17 parts of hollow glass microspheres, 2 parts of methacryloyl chromium complex and 25 parts of glass powder, 4 parts of curing agent, and 3 parts of leveling agent.

[0043] The particle size of the manganese zinc ferrite nanoparticles is in the range of 150 nm.

[0044] The weight average molecular weight of the dihydroxy tetra-active hydrogen unsaturated siloxane is 5000.

[0045] A process for coating a power transmission conductor with passive temperature reduction and capacity increase functions comprises the following steps: S1, adding manganese zinc ferrite nanoparticles into a grinder, and adding 15% oleic acid for mixed grinding, drying the residual liquid of the product after grinding, and collecting it by adsorption with a magnetic material to obtain manganese zinc ferrite nanopowder after drying; S2, adding terminal hydroxy dimethyl polysiloxane, nano silicon dioxide, silicon nitride, and mica powder into a mixer, mixing and stirring, and filtering to obtain a first mixed material; S3, after the mixer is rinsed and dried, polyethylene resin, dihydroxy tetra-active hydrogen unsaturated siloxane, isocyanic acid and fatty acid ester are added to the mixer for mixing reaction, the reaction time is 130 min, the reaction temperature is 60° C., and a second mixture is obtained; S4, re-weighing and proportioning the manganese-zinc ferrite nanopowder, the first mixed material and the second mixed material according to parts by mass, and setting aside; S5, after the mixer is rinsed and dried again, the proportioned manganese-zinc ferrite nano powder, the first mixed material and the second mixed material are added into the mixer, mixed and stirred to obtain a finished protective coating; S6, placing the hollow glass microspheres and glass powder in a NaOH solution, stirring at 65° C. for 2.5 h, then washing with deionized water and alcohol alternately, filtering under reduced pressure to remove excess water, and drying to obtain pretreated hollow glass microspheres and glass powder; S7. Mix methacryloyl chromium complex, silane coupling agent and aluminate coupling agent to obtain a composite coupling agent, then add the composite coupling agent to an ethanol solution, adjust the pH to 6.0, hydrolyze for 1.5 hours to obtain a hydrolyzed coupling agent solution, then add the pretreated hollow glass microbeads and glass powder to the hydrolyzed coupling agent solution, stir for 3.5 hours at 55°C, then wash alternately with deionized water and alcohol, dry at 75°C for 11 hours, then add a curing agent and a leveling agent, stir and mix, and obtain component B.

[0046] In step S5, the stirring speed is 325 rpm, the stirring time is 62 min, and the stirring temperature is 37°C.

[0047] The equipment used in the process of coating the power transmission wire with the passive temperature reduction and capacity increase function in this embodiment are all existing conventional equipment.

[0048] Embodiment 2 A transmission line coating with passive temperature reduction and capacity increase functions, wherein component A is composed of the following raw materials in parts by mass: 13 parts of manganese zinc ferrite nanoparticles, 33 parts of terminal hydroxy dimethyl polysiloxane, 15 parts of nano silicon dioxide, 11 parts of silicon nitride, 5 parts of mica powder, 15 parts of polyethylene resin, 60 parts of dihydroxy tetraactive hydrogen unsaturated siloxane, 10 parts of isocyanate, and 10 parts of fatty acid ester; component B is composed of the following raw materials in parts by mass: 5 parts of silane coupling agent, 7 parts of aluminate coupling agent, 17 parts of hollow glass microspheres, 2 parts of methacryloyl chromium complex and 25 parts of glass powder, 4 parts of curing agent, and 3 parts of leveling agent.

[0049] The particle size of the manganese zinc ferrite nanoparticles is in the range of 150 nm.

[0050] The weight average molecular weight of the dihydroxy tetraactive hydrogen unsaturated siloxane is 5,000.

[0051] A process for coating a power transmission conductor with passive temperature reduction and capacity increase functions comprises the following steps: S1, adding manganese zinc ferrite nanoparticles into a grinder, and adding 15% oleic acid for mixed grinding, drying the residual liquid of the product after grinding, and collecting it by adsorption with a magnetic material to obtain manganese zinc ferrite nanopowder after drying; S2, adding terminal hydroxy dimethyl polysiloxane, nano silicon dioxide, silicon nitride, and mica powder into a mixer, mixing and stirring, and filtering to obtain a first mixed material; S3, after the mixer is rinsed and dried, polyethylene resin, dihydroxy tetra-active hydrogen unsaturated siloxane, isocyanic acid and fatty acid ester are added to the mixer for mixing reaction, the reaction time is 130 min, the reaction temperature is 60° C., and a second mixture is obtained; S4, re-weighing and proportioning the manganese-zinc ferrite nanopowder, the first mixed material and the second mixed material according to parts by mass, and setting aside; S5, after the mixer is rinsed and dried again, the proportioned manganese-zinc ferrite nano powder, the first mixed material and the second mixed material are added into the mixer, mixed and stirred to obtain a finished protective coating; S6, placing the hollow glass microspheres and glass powder in a NaOH solution, stirring at 65° C. for 2.5 h, then washing with deionized water and alcohol alternately, filtering under reduced pressure to remove excess water, and drying to obtain pretreated hollow glass microspheres and glass powder; S7. Mix methacryloyl chromium complex, silane coupling agent and aluminate coupling agent to obtain a composite coupling agent, then add the composite coupling agent to an ethanol solution, adjust the pH to 6.0, hydrolyze for 1.5 hours to obtain a hydrolyzed coupling agent solution, then add the pretreated hollow glass microbeads and glass powder to the hydrolyzed coupling agent solution, stir for 3.5 hours at 55°C, then wash alternately with deionized water and alcohol, dry at 75°C for 11 hours, then add a curing agent and a leveling agent, stir and mix, and obtain component B.

[0052] In step S5, the stirring speed is 325 rpm, the stirring time is 62 min, and the stirring temperature is 37°C.

[0053] like Figure 2-10 As shown, the equipment used in steps S1-S5 is a protective coating processing device, which includes a grinder 1 and a mixer 4. The discharge port 29 of the grinder 1 is connected to a first storage box 2. The upper end of the mixer 4 is fixed with a first weighing box 5 and a second weighing box 6 through a feed pipe 40. The first storage box 2 is connected to the first weighing box 5 through a first conveying component 3. The discharge port 29 of the mixer 4 is connected to a second storage box 7 and a third storage box 8 through a discharge pipe. The second storage box 7 is connected to the second weighing box 5 through a second conveying component 9. The mixer 4 is connected to the mixing box 6, the third material storage box 8 is connected to the second material weighing box 6 through the third conveying assembly 10, a stirring assembly 12 is arranged inside the mixer 4, a filter screen 37 is fixed inside the mixer 4, a sewage pipe 39 and a slag discharge pipe 38 are fixed on the side of the mixer 4, a feed hopper 11 is fixed at the upper end of the mixer 4, a water adding pipe 13 is fixed at the upper end of the mixing box, a spray seat 36 is fixed at the upper end of the mixing box, the spray seat 36 is connected to the water adding pipe 13, the water adding pipe 13 is connected to an external high-pressure water pump, and a drying unit is arranged inside the mixing box.

[0054] With the above structure, during operation, manganese zinc ferrite nanoparticles are added into the grinder 1, and 15% oleic acid is added for mixed grinding. After grinding, the residual liquid of the product is dried, and after drying, it is adsorbed and collected by magnetic material to obtain manganese zinc ferrite nanopowder, and sent to the first storage box 2 for storage. At the same time, terminal hydroxy dimethyl polysiloxane, nano silicon dioxide, silicon nitride, and mica powder are added into the mixer 4 for mixed stirring, and filtered. The first mixed material is sent into the second storage box 7, and then the external high-pressure water pump is turned on, and the high-pressure cleaning liquid is sent into the spray seat 36 through the water supply pipe 13. The mixer 4 is cleaned by the spray seat 36 in cooperation with the stirring component 12. At the same time, the sewage pipe 39 and the slag discharge pipe 38 are opened to discharge the impurities filtered on the filter screen 37 and the sewage generated by the cleaning, and then the drying unit is used for cleaning. After drying, polyethylene resin, dihydroxy tetra-active hydrogen unsaturated siloxane, isocyanate and fatty acid ester are added to the mixer 4 for mixing reaction. The reaction time is 130 minutes and the reaction temperature is 60°C. The second mixture is then sent to the third storage box 8 for storage. The mixer 4 is rinsed and dried again by the spray seat 36 and the drying unit. The manganese zinc ferrite nano powder is sent to the first weighing box 5 through the first conveying component 3, and the first mixture is sent to the mixing box through the second conveying unit. After weighing according to the proportion, the manganese zinc ferrite nano powder and the first mixture are added to the mixer 4 for mixing and stirring. At the same time, the second mixture is sent to the second weighing box 6 by the third conveying component 10. After weighing, it is added to the mixer 4 for mixing and stirring to obtain a finished protective coating.

[0055] A feeding hopper 14 is fixed to the upper end of the grinder 1, a grinding motor 15 is fixed to the upper end of the grinder 1, a rotating cylinder 16 is fixed to the output shaft end of the grinding motor 15, a rotating column 17 is slidably connected to the interior of the rotating cylinder 16 through a slide rail, a grinding seat 18 is fixed to the lower end of the rotating column 17, a screening plate 20 matched with the grinding seat 18 is fixed to the interior of the grinder 1, the screening holes on the screening plate 20 are distributed in a ring shape in multiple rows, a blocking mechanism matched with the screening plate 20 is provided inside the grinder 1, a material cavity is formed between the lower side of the screening plate 20 and the grinder 1, a connecting port is provided between the first material storage box 2 and the material cavity, a rotating motor 22 is fixed to the interior of the grinder 1, a circular plate 23 located in the connecting port is fixed to the output shaft end of the rotating motor 22, a plurality of magnetic plates 32 and non-magnetic plates 31 are fixed to the outer periphery of the circular plate 23, the magnetic plates 32 and non-magnetic plates 31 are arranged alternately, a scraper cover 24 is fixed to the interior of the first material storage box 2, and the inner side of the scraper cover 24 is connected to the magnetic plate 32 And the upper and lower surfaces of the non-magnetic plate 31 are in conflict, and a number of leakage holes 33 are provided on the non-magnetic plate 31. A number of first heating rods 25 are fixed inside the grinding seat 18, and a number of screw conveyors 19 are fixed inside the grinding seat 18. The lower end of the spiral conveying blade of the screw conveyor 19 extends out of the lower end of the grinding seat 18, and the discharge port of the screw conveyor 19 is located at the inner upper part of the grinder 1, and an annular seat 26 is fixed inside the grinder 1, and a guide groove is provided on the inner periphery of the annular seat 26. A number of guide rods 28 are fixed on the outer periphery of the grinding seat 18, and the guide rods 28 are slidably connected with the guide groove. The guide groove includes a first straight section, a second straight section, an ascending section and a descending section. The two ends of the second straight section are respectively connected to the ascending section and the descending section, and the other ends of the ascending section and the descending section are connected to the first straight section. The bottom of the guide groove is an inclined mechanism, and the bottom of the guide groove 27 is provided with an inclined discharge port 29. The cross-section of the inner part of the guide rod 28 mixer 27 is the same as the cross-section of the guide groove 27.

[0056] With the above structure, during operation, the manganese-zinc-ferrite nanoparticles are added into the grinder 1 through the feeding hopper 14, and then 15% oleic acid is added, and the grinding motor 15 is turned on at the same time. The grinding motor 15 drives the grinding seat 18 to rotate through the rotating cylinder 16 and the rotating column 17, and the manganese-zinc-ferrite nanoparticles are ground by the cooperation of the grinding seat 18 and the screening plate 20. When the grinding seat 18 rotates, it will drive the guide rod 28 to slide in the guide groove 27. The ascending section and the descending section of the guide groove 27 are connected. Under the action of the ascending section and the descending section, the grinding seat 18 will be driven to move up and down intermittently, so that the manganese-zinc-ferrite nanoparticles with large particle size enter between the grinding seat 18 and the screening plate 20. At the same time, the descending of the grinding seat 18 can also be used to squeeze the manganese-zinc-ferrite nanoparticles, which greatly improves the grinding efficiency and grinding effect. At the same time, the screw conveyor 19 is intermittently turned on to transport the manganese-zinc-ferrite nanopowder between the grinding seat 18 and the screening plate 20 to the top of the material, so that other manganese-zinc-ferrite The ferrite nanoparticles can be ground to ensure the uniformity of grinding. After the grinding is completed, the first heating rod 25 is turned on to dry the residual liquid in the manganese-zinc ferrite nanopowder. After the drying is completed, the blocking mechanism is turned on to make the manganese-zinc ferrite nanopowder fall from the screening hole into the material chamber, and the rotating motor 22 is turned on at the same time. The rotating motor 22 drives the magnetic plate 32 and the non-magnetic plate 31 to rotate, and the manganese-zinc ferrite nanopowder is collected by the magnetic plate 32. Then, after rotating into the first storage box 2, the manganese-zinc ferrite nanopowder on the magnetic plate 32 is scraped off by the scraping cover 24 and falls into the first storage box 2, completing the magnetic separation operation of the manganese-zinc ferrite nanopowder to ensure the purity of the manganese-zinc ferrite nanopowder. The structure has good collection effect and high efficiency. At the same time, the interval between the magnetic plate 32 and the non-magnetic plate 31 makes the manganese-zinc ferrite nanopowder in the material chamber have a certain up and down oscillation, so that other substances on the manganese-zinc ferrite nanopowder can be shaken off, further improving the quality of the manganese-zinc ferrite nanopowder.

[0057] The sealing assembly includes a sealing frame 21, an outer gear ring 30 is fixed to the outer periphery of the sealing frame 21, an annular groove is opened inside the grinder 1, the outer gear ring 30 is rotatably connected to the annular groove, a driving motor 34 is fixed inside the grinder 1, a driving gear 35 is fixed to the output shaft end of the driving motor 34, the driving gear 35 is meshed with the outer gear ring 30, and the annular frame is composed of a plurality of sealing plates distributed in an annular shape.

[0058] With the above structure, when the manganese-zinc ferrite nanoparticles are ground, the blocking plate blocks the screening holes on the screening plate 20. After the grinding is completed, the driving motor 34 drives the driving gear 35 to rotate, and the driving gear 35 drives the blocking frame 21 to rotate through the outer gear ring 30, so that the blocking plate deviates from the screening holes, so that the manganese-zinc ferrite nanopowder after grinding can fall. The structure is simple, the degree of automation is high, and the difficulty of the work is reduced.

[0059] A cleaning assembly is provided in the feed pipe 40 and the feed hopper 11, and the cleaning assembly includes a second heating rod 42. A cleaning cavity 41 is opened in the side walls of the feed pipe 40 and the feed hopper 11, and the second heating rod 42 is fixed in the cleaning cavity 41. An electromagnetic block is fixed inside the cleaning cavity 41, and a spring 44 is fixed on the electromagnetic block. A knocking block 45 is fixed to the other end of the spring 44.

[0060] With the above structure, after the feeding is completed, the second heating rod 42 can be turned on to heat the feed pipe 40 and the feed hopper 11, and the material remaining on the inner walls of the feed pipe 40 and the feed hopper 11 can be dried. At the same time, the electromagnet 43 is intermittently powered on and off, and the spring 44 is used to make the knocking block 45 knock on the feed pipe 40 and the feed hopper 11, so that the feed pipe 40 and the feed hopper 11 vibrate, thereby shaking off the material remaining on the inner walls of the feed pipe 40 and the feed hopper 11. The setting of this structure can, on the one hand, ensure that the feed pipe 40 and the feed hopper 11 are not blocked by the material remaining on the inner walls for a long time, and on the other hand, prevent the material remaining on the inner walls of the feed pipe 40 and the feed hopper 11 from affecting the processing quality.

[0061] Embodiment 3 A transmission line coating with passive temperature reduction and capacity increase functions is composed of the following raw materials in parts by mass: 10 parts of manganese zinc ferrite nanoparticles, 40 parts of terminal hydroxy dimethyl polysiloxane, 10 parts of nano silicon dioxide, 15 parts of silicon nitride, 2 parts of mica powder, 20 parts of polyethylene resin, 50 parts of dihydroxy tetraactive hydrogen unsaturated siloxane, 13 parts of isocyanate, and 6 parts of fatty acid ester; component B is composed of the following raw materials in parts by mass: 8 parts of silane coupling agent, 4 parts of aluminate coupling agent, 20 parts of hollow glass microspheres, 1 part of methacryloyl chromium complex and 30 parts of glass powder, 2 parts of curing agent, and 4 parts of leveling agent.

[0062] The particle size of the manganese zinc ferrite nanoparticles is in the range of 200 nm.

[0063] The weight average molecular weight of the dihydroxy tetra-active hydrogen unsaturated siloxane is 3,500.

[0064] A process for coating a power transmission conductor with passive temperature reduction and capacity increase functions comprises the following steps: S1, adding manganese zinc ferrite nanoparticles into a grinder, and adding 25% oleic acid for mixed grinding, drying the residual liquid of the product after grinding, and collecting it by adsorption with a magnetic material to obtain manganese zinc ferrite nanopowder after drying; S2, adding terminal hydroxy dimethyl polysiloxane, nano silicon dioxide, silicon nitride, and mica powder into a mixer, mixing and stirring, and filtering to obtain a first mixed material; S3, after the mixer is rinsed and dried, polyethylene resin, dihydroxy tetra-active hydrogen unsaturated siloxane, isocyanic acid and fatty acid ester are added to the mixer for mixing reaction, the reaction time is 100 min, the reaction temperature is 70° C., and a second mixture is obtained; S4, re-weighing and proportioning the manganese-zinc ferrite nanopowder, the first mixed material and the second mixed material according to parts by mass, and setting aside; S5, after the mixer is rinsed and dried again, the proportioned manganese-zinc ferrite nano powder, the first mixed material and the second mixed material are added into the mixer, mixed and stirred to obtain a finished protective coating; S6, placing the hollow glass microspheres and glass powder in a NaOH solution, stirring at 70° C. for 2 h, then washing with deionized water and alcohol alternately, filtering under reduced pressure to remove excess water, and drying to obtain pretreated hollow glass microspheres and glass powder; S7. Mix methacryloyl chromium complex, silane coupling agent and aluminate coupling agent to obtain a composite coupling agent, then add the composite coupling agent to an ethanol solution, adjust the pH to 7.0, hydrolyze for 1 hour to obtain a hydrolyzed coupling agent solution, then add the pretreated hollow glass microbeads and glass powder to the hydrolyzed coupling agent solution, stir for 3 hours at 60°C, then wash with deionized water and alcohol alternately, dry at 80°C for 10 hours, and then add a curing agent and a leveling agent, stir and mix to obtain component B.

[0065] In step S5, the stirring speed is 200 rpm, the stirring time is 75 min, and the stirring temperature is 30°C.

[0066] The process of the power transmission wire coating with passive temperature reduction and capacity increase function in this embodiment uses the same processing equipment as that in the second embodiment, and the difference lies in the formula ratio and processing conditions.

[0067] Embodiment 4 A transmission line coating with passive temperature reduction and capacity increase functions is composed of the following raw materials in parts by mass: 25 parts of manganese zinc ferrite nanoparticles, 25 parts of terminal hydroxy dimethyl polysiloxane, 20 parts of nano silicon dioxide, 8 parts of silicon nitride, 8 parts of mica powder, 10 parts of polyethylene resin, 70 parts of dihydroxy tetra-active hydrogen unsaturated siloxane, 7 parts of isocyanate, and 14 parts of fatty acid ester; component B is composed of the following raw materials in parts by mass: 3 parts of silane coupling agent, 10 parts of aluminate coupling agent, 15 parts of hollow glass microspheres, 3 parts of methacryloyl chromium complex and 20 parts of glass powder, 6 parts of curing agent, and 1 part of leveling agent.

[0068] The particle size of the manganese zinc ferrite nanoparticles is in the range of 100 nm.

[0069] The weight average molecular weight of the dihydroxy tetra-active hydrogen unsaturated siloxane is 7,500.

[0070] A process for coating a power transmission conductor with passive temperature reduction and capacity increase functions comprises the following steps: S1, adding manganese zinc ferrite nanoparticles into a grinder, and adding 5% oleic acid for mixed grinding, drying the residual liquid of the product after grinding, and collecting it by adsorption with a magnetic material to obtain manganese zinc ferrite nanopowder after drying; S2, adding terminal hydroxy dimethyl polysiloxane, nano silicon dioxide, silicon nitride, and mica powder into a mixer, mixing and stirring, and filtering to obtain a first mixed material; S3, after the mixer is rinsed and dried, polyethylene resin, dihydroxy tetra-active hydrogen unsaturated siloxane, isocyanic acid and fatty acid ester are added to the mixer for mixing reaction, the reaction time is 160 min, the reaction temperature is 50° C., and a second mixture is obtained; S4, re-weighing and proportioning the manganese-zinc ferrite nanopowder, the first mixed material and the second mixed material according to parts by mass, and setting aside; S5, after the mixer is rinsed and dried again, the proportioned manganese-zinc ferrite nano powder, the first mixed material and the second mixed material are added into the mixer, mixed and stirred to obtain a finished protective coating; S6, placing the hollow glass microspheres and glass powder in a NaOH solution, stirring at 60° C. for 3 h, then washing with deionized water and alcohol alternately, filtering under reduced pressure to remove excess water, and drying to obtain pretreated hollow glass microspheres and glass powder; S7. Mix methacryloyl chromium complex, silane coupling agent and aluminate coupling agent to obtain a composite coupling agent, then add the composite coupling agent to an ethanol solution, adjust the pH to 5.0, hydrolyze for 2 hours to obtain a hydrolysis coupling agent solution, then add the pretreated hollow glass microbeads and glass powder to the hydrolysis coupling agent solution, stir at 50°C for 4 hours, then wash with deionized water and alcohol alternately, dry at 70°C for 12 hours, and then add a curing agent and a leveling agent, stir and mix to obtain component B.

[0071] In step S5, the stirring speed is 450 rpm, the stirring time is 50 min, and the stirring temperature is 45°C.

[0072] The process of the power transmission wire coating with passive temperature reduction and capacity increase function in this embodiment uses the same processing equipment as that in the second embodiment, and the difference lies in the formula ratio and processing conditions.

[0073] Experimental Example 1 The coating prepared in Example 1 and Example 4 was applied to the cable line coating as required, and relevant tests were performed. The results are as follows Fig.11 As shown: 1. The surface drying time is measured in accordance with GB / T 13477.5 and is expressed in min; 2. The curing speed is measured in accordance with GB / T 32369 and is expressed in mm / 24h; 3. The high temperature aging tensile strength and elongation at break are measured by using a high temperature aging box in accordance with GB / T 11026.1, 100°C*168h aging, and then using a tensile testing machine in accordance with GB / T1040.1-2018 to measure the tensile strength and elongation at break after aging, expressed in N / cm, %; 4. High temperature aging dielectric strength is measured using a high temperature aging chamber in accordance with GB / T 11026.1, after aging at 100°C*168h, the dielectric strength is measured in accordance with GB / T 31838.6 and is expressed in kV / mm; 5. Low-temperature aging tensile strength and elongation at break are measured using a low-temperature aging box in accordance with GB / T 2423.1, at -50°C*168h, and then using a tensile testing machine in accordance with GB / T1040.1-2018 to measure the tensile strength and elongation at break after aging, expressed in N / cm, %; 6. Low temperature aging dielectric strength is measured using a low temperature aging box according to GB / T 2423.1, after aging at -50℃*168h, the dielectric strength is measured according to GB / T 31838.6 and is expressed in kV / mm; According to the experimental data, the preparation devices for the protective coating in Example 1 and Example 2 are different, but the surface drying time, curing speed, high temperature aging tensile strength, low temperature aging tensile strength, high temperature aging elongation at break, low temperature aging elongation at break, high temperature aging dielectric strength, and low temperature aging dielectric strength of the protective coating in Example 2 are better than those in Example 1. Therefore, the use of the preparation device for the protective coating in the present invention can improve the surface drying time, curing speed, high temperature aging tensile strength, low temperature aging tensile strength, high temperature aging elongation at break, low temperature aging elongation at break, high temperature aging dielectric strength, and low temperature aging dielectric strength of the protective coating.

[0074] The preparation process conditions and formula ratios of the protective coating in Example 3, Example 4 and Example 2 are different. However, the surface drying time, curing speed, high temperature aging tensile strength, low temperature aging tensile strength, high temperature aging elongation at break, low temperature aging elongation at break, high temperature aging dielectric strength, and low temperature aging dielectric strength of the protective coating in Example 2 are better than those in Example 3 and Example 4. Therefore, different process conditions will also affect the surface drying time, curing speed, high temperature aging tensile strength, low temperature aging tensile strength, high temperature aging elongation at break, low temperature aging elongation at break, high temperature aging dielectric strength, and low temperature aging dielectric strength of the protective coating.

[0075] Comparative Example Existing uncoated high-voltage transmission wires are used.

[0076] Experimental Example 2 A composite structure four-split high-voltage transmission conductor current carrying capacity simulation evaluation system is used to simulate and evaluate the relationship between the sunshine intensity and the conductor current carrying capacity after the protective coating prepared in Examples 1 to 4 is applied; A composite structure four-split high-voltage transmission line current carrying capacity simulation and evaluation system comprises a wind speed simulation subsystem, a tension detection subsystem, a fixed test cabin and a mobile test cabin opposite to the fixed test cabin, a main control operation computer is arranged on the outside of the mobile test cabin, a sunshine simulation subsystem and a visual monitoring subsystem are arranged on the inside of the mobile test cabin, a cable temperature measurement subsystem and a temperature simulation subsystem are arranged inside the mobile test cabin and the fixed test cabin, a precipitation simulation subsystem, a coating subsystem and eight cable clamping subsystems are arranged on the fixed test cabin, the precipitation simulation subsystem, the cable clamping subsystem and the coating subsystem are arranged in order from top to bottom, the temperature simulation subsystem is located on the side of the cable clamping subsystem, and a cable data subsystem, a simulation subsystem, a current carrying capacity calculation and evaluation subsystem and an early warning subsystem are arranged inside the main control operation computer.

[0077] Simulate operating environment parameters: ambient temperature, ambient humidity, ambient wind speed, sunshine intensity and sunshine direction, etc.; Basic parameters of the experimental cable: outer diameter of the experimental cable, the age of the experimental cable, resistance per unit length of the experimental cable, stress of the experimental cable, voltage level, current size, etc.; Coating parameters: coating material and coating thickness, etc.

[0078] Use the controlled variable method: by keeping several parameters unchanged and changing only one of the variables, observe and analyze the impact of the variable on the result or phenomenon.

[0079] The following is the case where the coating parameters and the basic parameters of the experimental cable are kept the same, and the other simulated operating environment parameters except the sunlight intensity are kept the same. Taking sunlight intensity as a variable, the current carrying capacity simulation evaluation of the relationship between sunlight intensity and current carrying capacity (as well as the temperature of the experimental cable) is carried out.

[0080] Comparative example: The experimental cable is not coated with any material, and the sunlight intensity is gradually increased to obtain the changing relationship of the current carrying capacity (and wire temperature) of the high-voltage transmission wire without coating.

[0081] Example 1-4: Experimental cables were coated with the protective coating prepared in Example 1-4, and the sunlight intensity was gradually increased to obtain the relationship between the current carrying capacity (and the temperature of the wire) of the high-voltage transmission wire when the protective coating was applied. The experimental results are as follows Figure 12-15 As shown; According to experimental data, the conductor heats up as the intensity of sunlight increases, and the current carrying capacity decreases accordingly; The current carrying capacity of the high-voltage transmission wire after coating is significantly greater than that of the high-voltage transmission wire without coating, the wire temperature is low, and the coating has the effect of reflecting sunlight and dissipating heat.

[0082] The current carrying capacity of the high-voltage transmission wire coated with the protective coating is significantly greater than that of the uncoated high-voltage transmission wire, and the wire temperature is lower, that is, the protective coating has excellent sunlight reflection and heat dissipation effects.

[0083] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.

Claims

1. A power transmission wire coating with passive temperature reduction and capacity increase function, comprising component A and component B, characterized in that: Component A is composed of the following raw materials in parts by mass: 10-25 parts of manganese zinc ferrite nanoparticles, 25-40 parts of terminal hydroxy dimethyl polysiloxane, 10-20 parts of nano silicon dioxide, 8-15 parts of silicon nitride, 2-8 parts of mica powder, 10-20 parts of polyethylene resin, 50-70 parts of dihydroxy tetra-active hydrogen unsaturated siloxane, 7-13 parts of isocyanate, and 6-14 parts of fatty acid ester; Component B is composed of the following raw materials in parts by mass: 3-8 parts of silane coupling agent, 4-10 parts of aluminate coupling agent, 15-20 parts of hollow glass microspheres, 1-3 parts of methacryloyl chromium complex and 20-30 parts of glass powder, 2-6 parts of curing agent, and 1-4 parts of leveling agent.

2. The power transmission wire coating with passive temperature reduction and capacity increase function according to claim 1, characterized in that: Component A is composed of the following raw materials in parts by mass: 13 parts of manganese zinc ferrite nanoparticles, 33 parts of terminal hydroxy dimethyl polysiloxane, 15 parts of nano silicon dioxide, 11 parts of silicon nitride, 5 parts of mica powder, 15 parts of polyethylene resin, 60 parts of dihydroxy tetraactive hydrogen unsaturated siloxane, 10 parts of isocyanate, and 10 parts of fatty acid ester; Component B is composed of the following raw materials in parts by mass: 5 parts of silane coupling agent, 7 parts of aluminate coupling agent, 17 parts of hollow glass microspheres, 2 parts of methacryloyl chromium complex and 25 parts of glass powder, 4 parts of curing agent, and 3 parts of leveling agent.

3. The power transmission wire coating with passive temperature reduction and capacity increase function according to claim 1, characterized in that: The particle size of the manganese zinc ferrite nanoparticles ranges from 100 to 200 nm.

4. The power transmission wire coating with passive temperature reduction and capacity increase function according to claim 1, characterized in that: The weight average molecular weight of the dihydroxy tetra-active hydrogen unsaturated siloxane is 3500-7500.

5. The process for coating a power transmission wire with passive temperature reduction and capacity increase function as claimed in claim 1, characterized in that: The following steps are involved: S1, adding manganese zinc ferrite nanoparticles into a grinder, and adding 5%-25% oleic acid for mixed grinding, drying the residual liquid of the product after grinding, and collecting it by adsorption with a magnetic material to obtain manganese zinc ferrite nanopowder after drying; S2, adding terminal hydroxy dimethyl polysiloxane, nano silicon dioxide, silicon nitride, and mica powder into a mixer, mixing and stirring, and filtering to obtain a first mixed material; S3, after the mixer is rinsed and dried, polyethylene resin, dihydroxy tetra-active hydrogen unsaturated siloxane, isocyanic acid and fatty acid ester are added to the mixer for mixing reaction, the reaction time is 100-160min, the reaction temperature is 50-70°C, and the second mixture is obtained; S4, re-weighing and proportioning the manganese-zinc ferrite nanopowder, the first mixed material and the second mixed material according to parts by mass, and setting aside; S5, after the mixer is rinsed and dried again, the proportioned manganese-zinc ferrite nanopowder, the first mixed material and the second mixed material are added into the mixer, and mixed and stirred to obtain component A; S6, placing the hollow glass microspheres and glass powder in a NaOH solution, stirring at 60-70° C. for 2-3 hours, then washing with deionized water and alcohol alternately, filtering under reduced pressure to remove excess water, and drying to obtain pretreated hollow glass microspheres and glass powder; S7. Mix methacryloyl chromium complex, silane coupling agent and aluminate coupling agent to obtain a composite coupling agent, then add the composite coupling agent to an ethanol solution, adjust the pH to 5.0-7.0, hydrolyze for 1-2 hours to obtain a hydrolyzed coupling agent solution, then add the pretreated hollow glass microbeads and glass powder to the hydrolyzed coupling agent solution, stir at 50-60°C for 3-4 hours, then wash alternately with deionized water and alcohol, dry at 70-80°C for 10-12 hours, then add a curing agent and a leveling agent, stir and mix, and obtain component B.

6. The process for coating a power transmission wire with passive temperature reduction and capacity increase function according to claim 5, characterized in that: In step S5, the stirring speed is 200-450 rpm, the stirring time is 50-75 min, and the stirring temperature is 30-45°C.

7. The process for coating a power transmission wire with passive temperature reduction and capacity increase function according to claim 5, characterized in that: The equipment used in the steps S1-S5 is a protective coating processing device, which comprises a grinder (1) and a mixer (4), wherein the discharge port (29) of the grinder (1) is connected to a first material storage box (2), the upper end of the mixer (4) is fixed with a first weighing box (5) and a second weighing box (6) via a feed discharge pipe (40), the first material storage box (2) is connected to the first weighing box (5) via a first conveying component (3), the discharge port (29) of the mixer (4) is connected to a second material storage box (7) and a third material storage box (8) via a discharge pipe, the second material storage box (7) is connected to the second weighing box (6) via a second conveying component (9), The mixer (4) is connected to a mixing box (6), the third material storage box (8) is connected to the second material weighing box (6) through a third conveying assembly (10), a stirring assembly (12) is arranged inside the mixer (4), a filter screen (37) is fixed inside the mixer (4), a sewage discharge pipe (39) and a slag discharge pipe (38) are fixed on the side of the mixer (4), a feed hopper (11) is fixed at the upper end of the mixer (4), a water supply pipe (13) is fixed at the upper end of the mixing box, a spray seat (36) is fixed at the upper end of the mixing box, the spray seat (36) is connected to the water supply pipe (13), the water supply pipe (13) is connected to an external high-pressure water pump, and a drying unit is arranged inside the mixing box.

8. The process for coating a power transmission wire with passive temperature reduction and capacity increase function according to claim 7, characterized in that: The upper end of the grinding machine (1) is fixed with a feeding hopper (14), the upper end of the grinding machine (1) is fixed with a grinding motor (15), the output shaft end of the grinding motor (15) is fixed with a rotating cylinder (16), the interior of the rotating cylinder (16) is slidably connected with a rotating column (17) via a slide rail, the lower end of the rotating column (17) is fixed with a grinding seat (18), the interior of the grinding machine (1) is fixed with a screening plate (20) matched with the grinding seat (18), the screening holes on the screening plate (20) are arranged in a ring shape and have a plurality of rows, and the interior of the grinding machine (1) is provided with a screen plate (20) matched with the screening plate (20). 0) is provided, a material cavity is formed between the lower side of the screening plate (20) and the grinding machine (1), a communication port is provided between the first material storage box (2) and the material cavity, a rotating motor (22) is fixed inside the grinding machine (1), a circular plate (23) located in the communication port is fixed to the output shaft end of the rotating motor (22), a plurality of magnetic plates (32) and non-magnetic plates (31) are fixed to the outer periphery of the circular plate (23), the magnetic plates (32) and non-magnetic plates (31) are arranged in an alternating manner, a scraper cover (24) is fixed inside the first material storage box (2), and the scraper cover (24) The inner side of the grinding machine (1) contacts the upper and lower surfaces of the magnetic plate (32) and the non-magnetic plate (31); the non-magnetic plate (31) is provided with a plurality of leakage holes (33); a plurality of first heating rods (25) are fixed inside the grinding seat (18); a plurality of screw conveyors (19) are fixed inside the grinding seat (18); the lower ends of the screw conveyor blades of the screw conveyors (19) extend out of the lower end of the grinding seat (18); the discharge port of the screw conveyors (19) is located at the inner upper part of the grinding machine (1); an annular seat (26) is fixed inside the grinding machine (1); the inner portion of the annular seat (26) A guide slot is provided around the grinding seat (18). A plurality of guide rods (28) are fixed on the outer periphery of the grinding seat (18). The guide rods (28) are slidably connected to the guide slots. The guide slots include a first straight section, a second straight section, an ascending section and a descending section. The two ends of the second straight section are respectively connected to the ascending section and the descending section. The other ends of the ascending section and the descending section are connected to the first straight section. The bottom of the guide slot is an inclined mechanism. An inclined discharge port (29) is provided at the bottom of the guide slot (27). The cross section of the guide rod (28) inside the mixer (27) is the same as the cross section of the guide slot (27).

9. The process for coating a power transmission wire with passive temperature reduction and capacity increase function according to claim 8, characterized in that: The blocking assembly comprises a blocking frame (21), an outer gear ring (30) is fixed to the outer periphery of the blocking frame (21), an annular groove is provided inside the grinder (1), the outer gear ring (30) is rotatably connected to the annular groove, a driving motor (34) is fixed inside the grinder (1), a driving gear (35) is fixed to the output shaft end of the driving motor (34), the driving gear (35) is meshed with the outer gear ring (30), and the annular frame is composed of a plurality of annularly distributed blocking plates.

10. The process for coating a power transmission line with passive temperature reduction and capacity increase function according to claim 7, characterized in that: The feed tube (40) and the feed hopper (11) are both provided with a cleaning assembly, the cleaning assembly comprising a second heating rod (42), a cleaning cavity (41) is provided in the side walls of the feed tube (40) and the feed hopper (11), the second heating rod (42) is fixed in the cleaning cavity (41), an electromagnetic block is fixed inside the cleaning cavity (41), a spring (44) is fixed on the electromagnetic block, and a knocking block (45) is fixed to the other end of the spring (44).

Citation Information

Patent Citations

  • Wire with high current-carrying capacity and icing preventing performance and manufacturing method thereof

    CN103985464A

  • Wire with high ampacity and anti-icing performance and preparation method thereof

    CN103985464B

  • Anti-aging polyethylene pipe and preparation method thereof

    CN113652168A

  • High-thermal-conductivity voltage-resistant insulating paint as well as preparation method and application thereof

    CN118374224A